EFFECT OF PRODUCT QUALITY, PROMOTION, AND BRAND IMAGE ON PURCHASE DECISION OF NIKE SPORTS SHOES (Case Study On S1 FISIP UNDIP Students) - Denny Saputra; Handoyo Djoko Waluyo; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2014)
Complex consumer needs all critical and followed increasingly competitive market competition lead to Nike Sports Shoes must to compete and also maintain their market consumer seized from its competitors. Consumers who take the decision to choose Nike Sports Shoes will consider various things before buying it. Consideration to make a decision consist of influenced the quality of the product, promotion, and brand image of Nike Sport Shoes. The problem in this research is Sports Shoes Nike fluctuation data during 2011 until 2013 seen from Top Brand Index. The research used explanatory research approach by collect data using questionnaire with a sample of 97 respondents in the S1 FISIP UNDIP students. Collection data used purposive sampling technique based on certain assumptions. Analysis techniques using validity test, reliability test, simple linear regression, multiple linear regression, t test, F test by SPSS 20.0 programs.Based on the results of statistical calculation with linear regression analysis can be shown by the regression equation Y = 4.261 + 0.073 X1 - X2 0.031 + 0.815 X3, from the regression equation is known that the quality of the product, promotion, and brand image has a positive influence on purchasing decisions. The results of the calculation of the determination coefficient is 0.429. It shows that the quality of product, promotion and brand image explain about purchase decision in 42.9% and 57.1% explained by other variables that are not observed.Suggestions for the company consist of to keep innovate and create better product quality, increase the frequency of advertising and sales promotion, and select great and appropriate brand ambassador.Complex consumer needs all critical and followed increasingly competitive market competition lead to Nike Sports Shoes must to compete and also maintain their market consumer seized from its competitors. Consumers who take the decision to choose Nike Sports Shoes will consider various things before buying it. Consideration to make a decision consist of influenced the quality of the product, promotion, and brand image of Nike Sport Shoes. The problem in this research is Sports Shoes Nike fluctuation data during 2011 until 2013 seen from Top Brand Index. The research used explanatory research approach by collect data using questionnaire with a sample of 97 respondents in the S1 FISIP UNDIP students. Collection data used purposive sampling technique based on certain assumptions. Analysis techniques using validity test, reliability test, simple linear regression, multiple linear regression, t test, F test by SPSS 20.0 programs.Based on the results of statistical calculation with linear regression analysis can be shown by the regression equation Y = 4.261 + 0.073 X1 - X2 0.031 + 0.815 X3, from the regression equation is known that the quality of the product, promotion, and brand image has a positive influence on purchasing decisions. The results of the calculation of the determination coefficient is 0.429. It shows that the quality of product, promotion and brand image explain about purchase decision in 42.9% and 57.1% explained by other variables that are not observed.Suggestions for the company consist of to keep innovate and create better product quality, increase the frequency of advertising and sales promotion, and select great and appropriate brand ambassador.